Environmental performance toolkit for glazed façades - Lim, Kai (CIBSE, 2004)
This publication is based on a 2 year Partners-in-Innovation (PII) project sponsored by the Department of Trade and Industry, that conducted a comprehensive study on the overall performance of highly glazed facades. --